"No seconds for you!": Exploring a sociocultural model of fat-talking in the presence of family involving restrictive/critical caregiver eating messages, relational body image, and anti-fat attitudes in college women. (September 2019) - Rogers, Courtney B.; Taylor, Jessica J.; Jafari, Nadia; Webb, Jennifer B.
Highlights: Restrictive/critical caregiver eating messages correlated with family fat talk. Relational body image and anti-fat attitudes were mediators. External body shame was the strongest mediator. Implications for theory and practice are discussed. Abstract: In line with sociocultural models of parental influence on body image, we examined the relationship between recall of restrictive/critical caregiver eating messages (RCEM) and current frequency of disclosing self-disparaging fat talk among family in 335 undergraduate women ( M age  = 19.4; SD  = 1.53; range = 18–27). Additionally, two forms of relational body image (i.e., perceived body acceptance by others, external body image shame) and anti-fat attitudes were tested as potential explanatory pathways. RCEM were positively related to current frequency of self-directed fat talk in the family context. All three proposed mediators helped explain this relationship, with external body image shame demonstrating the largest observed effect. Findings suggest frequent recollections of caregivers' implied weight-stigmatizing comments surrounding eating may contribute to more frequent self-denigrating body talk with family members at present via both positive and negative dimensions of relational body image and endorsed explicit weight bias. Theoretical and practical implications are discussed.